Rhetoric by Avistotel: a Legal View - K. Kh. Rekosh (Vestnik MGIMO-Universiteta)
Analysis of any phenomenon, which is far from the researcher for thousands years, in the light of this or that department of knowledge, highlights one and obscures another, prefers one over another. It happened to the rhetoric which was snatched by philology and neglected by lawyers. Although nowadays it is natural that the same phenomena are studied by different Sciences, the ancient rhetoric is looked at by most researchers as the art of philology. But the approach by Aristotle, in his Rhetoric, was legal rather than linguistic. Among the Aristotle's 4 requirements concerning good style (correctness, clarity, relevance and eloquence) eloquence is only % and the % are closer to the law. Rhetoric has incorporated all the features of linguistic mechanisms and gave them to the law. The law perceived moral and ethical ideas: the good justice, virtue, ritual, law and techniques of philology and persuasion, among which the main one is syllogism already used in the dialectic, the main logic principle of legal reasoning. Towards the past, rhetoric is parallel to dialectic, but dialectic is focused on one person or on the speaker, and rhetoric aims at the audience, the first one tries to convince himself and the second tries to convince the audience and in this role rhetoric is linked with the law. As far as the evolution of law is concerned, instead of legal technique there was rhetoric (especially in its methodological form, defined by Aristotle), which can be considered as a step towards creating the law as a design in ancient Greece. It is proved by a comparison of the ancient institution of judicial process and judicial speeches with modern legal technicalities, which shows that the legal machinery embraced the principles of "rhetorical" technique. The methodological nature of the rhetoric by Aristotle is usually overlooked by linguists and lawyers.